2013
DOI: 10.1021/cb400508k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Glucan in Mycobacteria Involves a Hetero-octameric Complex of Trehalose Synthase TreS and Maltokinase Pep2

Abstract: Recent evidence established that the cell envelope of Mycobacterium tuberculosis, the bacillus causing tuberculosis (TB), is coated by an α-glucan-containing capsule that has been implicated in persistence in a mouse infection model. As one of three known metabolic routes to α-glucan in mycobacteria, the cytoplasmic GlgE-pathway converts trehalose to α(1 → 4),α(1 → 6)-linked glucan in 4 steps. Whether individual reaction steps, catalyzed by trehalose synthase TreS, maltokinase Pep2, and glycosyltransferases Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 37 publications
3
72
0
Order By: Relevance
“…More importantly, the formation of the complex enhances the activity of Mtb MaK by 3-folds7. Although the crystal structure of the tetramer of TreS is known71718, the molecular basis for the enhancement of activity of MaK by TreS is currently not understood. In addition, the structural basis for conversion of maltose to maltose-1-phosphate is not known.…”
mentioning
confidence: 99%
“…More importantly, the formation of the complex enhances the activity of Mtb MaK by 3-folds7. Although the crystal structure of the tetramer of TreS is known71718, the molecular basis for the enhancement of activity of MaK by TreS is currently not understood. In addition, the structural basis for conversion of maltose to maltose-1-phosphate is not known.…”
mentioning
confidence: 99%
“…Disruption of glgE , like that of glgB , results in the accumulation of maltose-1-phosphate which is toxic to the cells. The crystal structures of TreS from both Mtb and M. smegmatis were recently reported (Roy et al ., 2013; Caner et al ., 2013) and the mechanism of association of the C-ter domain of this enzyme with oligosaccharides and possibly glycogen investigated (Caner et al ., 2013). Importantly, it was found that TreS forms a hetero-octameric complex with Pep2.…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%
“…Importantly, it was found that TreS forms a hetero-octameric complex with Pep2. The formation of this complex boosts the maltokinase activity of Pep2 suggesting that it may serve to regulate α-(1,4)-glucan synthesis (Roy et al ., 2013). Another point of control of this pathway appears to be at the level of GlgE which was recently reported to be negatively phosphoregulated by the Ser/Thr kinase PknB (Leiba et al ., 2013).…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%
“…The catalytic mechanism of trehalose synthase involves a glucosyl-enzyme intermediate and the liberation of the other glucose ring. Quite how this enzyme ensures that the reaction is strictly intramolecular [20,21] is starting to become clearer with the elucidation of crystal structures in either open or closed conformations [22][23][24]. Its active site seems to be able to sterically prevent the escape of the transiently liberated glucose molecule.…”
Section: The Discovery Of the Glge Pathwaymentioning
confidence: 99%
“…Then maltose kinase, which has a somewhat unusual subunit architecture for a kinase [25,26], generates M1P from maltose [27][28][29][30]. Interestingly, maltose kinase and trehalose synthase form a hetero-octameric complex [23] that results in a higher maltose kinase activity. GlgE then generates linear polymers from M1P.…”
Section: The Discovery Of the Glge Pathwaymentioning
confidence: 99%